Potential Airborne Asbestos Exposure and Risk Associated with the Historical Use of Cosmetic Talcum Powder Products. Issue 10 (12th April 2019) - Burns, Amanda M.; Barlow, Christy A.; Banducci, Amber M.; Unice, Kenneth M.; Sahmel, Jennifer
Abstract: Over time, concerns have been raised regarding the potential for human exposure and risk from asbestos in cosmetic‐talc–containing consumer products. In 1985, the U.S. Food and Drug Administration (FDA) conducted a risk assessment evaluating the potential inhalation asbestos exposure associated with the cosmetic talc consumer use scenario of powdering an infant during diapering, and found that risks were below levels associated with background asbestos exposures and risk. However, given the scope and age of the FDA's assessment, it was unknown whether the agency's conclusions remained relevant to current risk assessment practices, talc application scenarios, and exposure data. This analysis updates the previous FDA assessment by incorporating the current published exposure literature associated with consumer use of talcum powder and using the current U.S. Environmental Protection Agency's (EPA) nonoccupational asbestos risk assessment approach to estimate potential cumulative asbestos exposure and risk for four use scenarios: (1) infant exposure during diapering; (2) adult exposure from infant diapering; (3) adult exposure from face powdering; and (4) adult exposure from body powdering. The estimated range of cumulative asbestos exposure potential for all scenarios (assuming an asbestos content of 0.1%) ranged from 0.0000021 to 0.0096 f/cc‐yr and resulted in risk estimates that were within or below EPA's acceptable target risk levels. Consistent with the original FDA findings, exposure and corresponding health risk in this range were orders of magnitude below upper‐bound estimates of cumulative asbestos exposure and risk at ambient levels, which have not been associated with increased incidence of asbestos‐related disease.